2014
DOI: 10.1017/s0950268813003397
|View full text |Cite
|
Sign up to set email alerts
|

Viral aetiology and clinico-epidemiological features of acute encephalitis syndrome in eastern India

Abstract: This study reports clinico-epidemiological features and viral agents causing acute encephalitis syndrome (AES) in the eastern Indian region through hospital-based case enrolment during April 2011 to July 2012. Blood and CSF samples of 526 AES cases were investigated by serology and/or PCR. Viral aetiology was identified in 91 (17·2%) cases. Herpes simplex virus (HSV; types I or II) was most common (16·1%), followed by measles (2·6%), Japanese encephalitis virus (1·5%), dengue virus (0·57%), varicella zoster vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
9
17
0
Order By: Relevance
“…Majority of cases belonged to < 15 years of age group (80%) which was similar to other studies conducted by Reena et al ( 2008, 67.5%) and Rathore et al (2014, 81%) [7,19]. Panagariya et al (2001) found AES was more common in pa ents of age > 40 years and < 20 years, male: Female ra o was 2:1 which is in accordance to our study where male to female ra o showed 2.1:1 with male preponderance [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Majority of cases belonged to < 15 years of age group (80%) which was similar to other studies conducted by Reena et al ( 2008, 67.5%) and Rathore et al (2014, 81%) [7,19]. Panagariya et al (2001) found AES was more common in pa ents of age > 40 years and < 20 years, male: Female ra o was 2:1 which is in accordance to our study where male to female ra o showed 2.1:1 with male preponderance [20].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 8 (8.9%) samples were tested posi ve for Herpes simplex virus 1&2, in PCR assay, which is similar to the studies by Beig et al (2010, 10.5%) [26], while being in contrast to studies conducted by Rathore et al (2014, 16.1%) [19]. Similarly 8 (8.9%) samples were found to be posi ve in ELISA assay which was in contrast to previous studies by Hanada et al (1988, 22.5%) [27].…”
Section: Discussionsupporting
confidence: 87%
“…Assam, a northeastern state in India, is recognized as an endemic zone for acute encephalitis syndrome (AES), especially that caused by Japanese encephalitis virus (JEV). However, the etiology of >50% of the AES cases in Assam remains unrecognized ( 4 ) . In this study, we aimed to determine the contribution of scrub typhus to AES in this region.…”
mentioning
confidence: 99%
“…However, in contrast to our results, a previous study revealed that aseptic encephalitis occurred more frequently in young adults despite of no direct comparison in age of onset between aseptic meningitis and encephalitis patients. 23 This discrepancy may be caused by different objects with variable viral pathogens. To confirm our results, identification of the viral pathogens may be needed.…”
Section: Discussionmentioning
confidence: 99%